PENGARUH MEDIA SEGEHAN TERHADAP PENGETAHUAN DAN KREATIVITAS SAINS PADA ANAK USIA DINI - Ni Luh Ika Windayani; Kadek Ari Wisudayanti (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the effect of Segehan media on the cognitive abilities and creativity of early childhood education (PAUD) students in learning science. This research employs experimental research methodologies. The population in this study consists of 59 students from group B of the Pemaron village kindergarten. The samples for this study were randomly selected to define the experimental and control classes. The data collection approach was conducted through observation, measured using research tools. The MANOVA test was performed to analyze the data. Based on the results of hypothesis testing, it can be concluded that the Segehan Sanga Warna learning technique has an impact on students' cognitive development and creativity compared to the direct learning method. Based on the findings of this study, it is recommended that PAUD educators consider the use of Segehan media as an alternative method in science learning. By integrating this technique, it is expected that students' cognitive abilities and creativity can be more effectively enhanced. Furthermore, additional research with a larger and more diverse population is necessary to strengthen these findings and ensure the generalization of the results. This implies that learning methods involving cultural and creative elements, such as Segehan, can be an effective approach in early childhood education. Therefore, educators and policymakers in the field of education should consider incorporating this method into the PAUD curriculum to achieve optimal learning outcomes.